Cybersecurity and Privacy Risk Assessment of Point-of-Care Systems in Healthcare—A Use Case Approach - Marc Jofre; Diana Navarro-Llobet; Ramon Agulló; Jordi Puig; Gustavo Gonzalez-Granadillo; Juan Mora Zamorano; Ramon Romeu (Applied Sciences, 2021)
Point-of-care systems are generally used in healthcare to respond rapidly and prevent critical health conditions. Hence, POC systems often handle personal health information; and consequently, their cybersecurity and privacy requirements are of crucial importance. While, assessing these requirements is a significant task. In this work, we propose a use case approach to assess specifications of cybersecurity and privacy requirements of POC systems in a structured and self-contained form. Such an approach is appropriate since use cases are one of the most common means adopted by developers to derive requirements. As a result, we detail a use case approach in the framework of a real-based healthcare IT infrastructure that includes a health information system, integration engines, application servers, web services, medical devices, smartphone apps and medical modalities (all data simulated) together with the interaction with participants. Since our use case also sustains the analysis of cybersecurity and privacy risks in different threat scenarios, it also supports decision making and the analysis of compliance considerations.